Severe Cutaneous Adverse Drug Reactions in Bangladesh: A Review in a Tertiary Level Hospital (Journal of Armed Forces Medical College, Bangladesh, 2016)
Introduction: The Severe Cutaneous Adverse Drug Reactions (SCADRs) are rare but life-threatening as these encompass drug reaction with eosinophilia and systemic symptoms (DRESS), Stevens-Johnson syndrome (SJS), toxic epidermal necrolysis (TEN) and acute generalized exanthematous pustulosis (AGEP).Objective: To estimate the incidence of SCADRs and to find out the cause in Bangladesh.Materials and Methods: 50 patients with SCADRs were studied over a period of 1 year from January 2015 to December 2015 in the Department of Dermatology, Combined Military Hospital, Dhaka. Data were collected from the informant and recorded in structured Case Report Form. Quantitative data were expressed as mean and standard deviation and qualitative data as frequency and percentage.Results: Clinical diagnosis of the study subjects recognized 46.0% cases as SJS, 28(19.0%) as TEN, 16.0% as DRESS and 10.0% as AGEP. The maximum incidence (46%) was seen in the age group of 31-50 years; mean age of the patient was 37.42+5.3 years. Male and female ratio was 2.84:1. Anticonvulsant group of drugs could give rise to maximum incidence of SCADRs. Carbamazepine was responsible in 22.0% cases of SCADRs, followed by Phenytoin in 16.0% patients and Phenobarbital in 14.0% cases.Conclusion: SCADRs were seen mostly with the anticonvulsant drugs belonging to Carbamazepine and Phenytoin group. SCADRs deserve continuous monitoring to plan preventive strategies.Journal of Armed Forces Medical College Bangladesh Vol.12(2) 2016: 71-75